Design of a bonnet of a sport vehicle realized with an innovative recyclable Polymeric Matrix Composite and virtual characterization of the related sandwich structure - Basso M. (EDP Sciences, 2021)
This article presents the design activities of an automotive component to be produced using a recyclable cleavable-epoxy Matrix Composite and Basalt-Derived Mineral Fibres. The material innovations are being studied within project C2CC (www.c2cc-project.eu), aimed at satisfying latest EU directives regarding end-of-life reuse and C-footprint reduction. The main targets are the weight reduction, obtained employing materials with lower footprint, namely a biomass derived epoxy and a cradle-to-cradle recyclable mineral fiber, that is a fibre that (differently from carbon fibre) can be remelted to long fibre with no decrease in mechanical specifications [1]. For recycling both the resin and the fibre, a the cleavable hardener was adopted [2] developed by Connnora Inc (US), which avoids the need of pyrolysis to recover and recycle the fibers from prepreg scraps and end-of-life components. The main project demonstrator is the front bonnet of segment A vehicle FIAT 500 Abarth. One approach to reach the component expected performances is using the semifinished composite materials (prepregs) produced by the project to manufacture a final structural sandwich. From the modelling point of view, this work carries out a multiscale approach starting from the basic constituents of skin and core and ending with the model at the mesoscale of the specimens of the sandwich. The simulation activity was conducted considering the possible recyclable sandwich cores, and the comparison aims at selecting the optimal ones for this specific automotive component.